Pitting behavior of SLM 316L stainless steel exposed to chloride environments with different aggressiveness: Pitting mechanism induced by gas pores. (1st May 2020) - Duan, Zhiwei; Man, Cheng; Dong, Chaofang; Cui, Zhongyu; Kong, Decheng; wang, Li; Wang, Xin
Highlights: Pitting corrosion of SLM 316L SS in different aggressive solutions was studied. A model was built to explain the pitting mechanism induced by gas-pore. Metastable pitting at covered gas-pores is more likely to transition into stable. Abstract: In this study, the pitting behaviors of wrought and SLM 316L SSs (stainless steels) are comparatively investigated under the conditions of different aggressiveness. The experimental results show that SLM 316L SS exhibits higher sensitivity to pitting corrosion in extremely aggressive solutions, while the wrought sample is more vulnerable to pitting in conditions with low aggressiveness. Gas pores are the pitting-sensitive sites in SLM 316L SS, and metastable pits initiated at covered gas pores are easier to evolve to stable growth compared to open pores due to the greater diffusion resistance.